ABORDAR LA SUSTENTABILIDAD DESDE LAS CIENCIAS AGRÍCOLAS - Villarruel Fuentes, Manuel (Universidad de Costa Rica, 2018)
Sustainability has significantly impacted the professional practice of Agronomy, with no clarity in the ways in which are concrete through its dominant practices. Therefore the way how sustainability is approached conceptually from the sciences was analyzed, its relationship with nature understood as a consumption good and a service provider, justifying in the process its accession to the technology as a means for social and economic development. On this basis the reconceptualization of sustainability within the interdisciplinary field of Agronomy arises as a new object of study that must be addressed by environmental education, work process approached from the critical methodology, based on the critical, logical and creative thinking, that emerges from a theoretical element of previous knowledge, looking to generate a new objective knowledge that allows to advance in the explanation and transformation of a concrete reality.